Faktor-faktor yang Berhubungan dengan Kelelahan Kerja Pada Perawat di Rumah Sakit Awal Bross Bekasi - Andrianus Evander Kondi; Herlina Herlina (Jurnal Persada Husada Indonesia, 2019)
Fatigue is an occupational health problem that needs special attention. Fatigue for everyone is subjective because it is related to feelings, because in addition to being influenced by physical and biological factors, fatigue is also influenced by psychological factors (psychology). This study aims to determine the factors that influence work fatigue in nurses at the Early Bross Hospital in Bekasi in 2018 with a sample of 60 respondents and data collected using a questionnaire. The object of this study was the nurse of the Bross Early Hospital. The design of this study is a descriptive analytic study using a quantitative approach. Independent variables (characteristics: age, sex, length of work). The dependent variable is work fatigue. The results obtained from this study that there is a significant effect between p-value age (0.001), p-value workload (0.001), p-value work attitude (0.001).